Perbandingan Sistem Hukum Indonesia Dengan Sistem Hukum Barat - Tri Mei Rosalya Purba; Sri Hadiningrum (Lembaga Pengembangan Kinerja Dosen, 2024)
Comparative law as a science in the Western world is a very young branch of science, only growing rapidly at the end of the 19th century or at the beginning of the 20th century. Previously, efforts had been made to compare several systems with each other, but at that time It cannot be said that research has been carried out using a comparative method carried out systematically and continuously with the aim of achieving a certain goal. The method used is library research, collecting data by searching for sources and constructing them from various sources such as books, journals and existing research. In its development, this legal system recognized the division of public law and private law. Public law includes legal regulations that regulate the power and authority of the ruler/state as well as the relationships between society and the state (the same as public law in the Anglo-Saxon legal system). Private Law includes legal regulations that regulate relationships between individuals in meeting their daily needs. The values ​​of the western legal system are not in accordance with the noble values ​​of the Indonesian nation, resulting in a gap between the law and the Indonesian society it regulates. The customary law system has its values ​​in certain indigenous communities, can only be believed and practiced by indigenous communities, and cannot be ratified as national law, and the Islamic legal system's values ​​are believed and practiced by the majority of Indonesian people nationally.